Quantity and Quality of Inhaled Dose Predicts Immunopathology in Tuberculosis - Fennelly, Kevin P.; Jones-López, Edward C. (Frontiers in Immunology, 2015)
Experimental animal models of tuberculosis (TB) have convincingly demonstrated that inhaled dose predicts immunopathology and survival. In contrast, the importance of inhaled dose has generally not been appreciated in TB epidemiology, clinical science, or the practice of TB control. Infectiousness of TB patients has traditionally been assessed using microscopy for acid-fast bacilli in the sputum, which should be considered only a risk factor. We have recently demonstrated that cough aerosol cultures from index cases with pulmonary TB are the best predictors of new infection among household contacts. We suggest that cough aerosols of M. tuberculosis are the best surrogates of inhaled dose, and we hypothesize that the quantity of cough aerosols is associated with TB infection versus disease. Although several factors affect the quality of infectious aerosols, we propose that the particle size distribution of cough aerosols is an important predictor of primary upper airway disease and cervical lymphadenitis and of immune responses in exposed hosts. We hypothesize that large droplet aerosols (>5 μ) containing M. tuberculosis deposit in the upper airway and can induce immune responses without establishing infection. We suggest that this may partially explain the large proportion of humans who never develop TB disease in spite of having immunological evidence of M. tuberculosis infection (e.g., positive tuberculin skin test or interferon gamma release assay). If these hypotheses are proven true, they would alter the current paradigm of latent TB infection and reactivation, further demonstrating the need for better biomarkers or methods of assessing TB infection and the risk of developing disease.